Soil quality and vulnerability in a Mediterranean natural ecosystem of Central Italy. - Francaviglia, R; Gataleta, L; Marchionni, M; Trinchera, A; Aromolo, R; Benedetti, A; Nisini, L; Morselli, L; Brusori, B; Olivieri, P; Bernardi, E (Chemosphere, 2004)
Wet and dry atmospheric depositions and soil chemical and microbiological properties were determined in a Mediterranean natural ecosystem of Central Italy near Rome (Castelporziano Estate). The monitoring of depositions permitted us to quantify the exceedances of S and N compounds (expressed as eqH(+)ha(-1)year(-1)) over the critical loads of acidity. Critical loads, i.e. the quantity of a substance which a part of the environment can tolerate without adverse effects occurring, were determined adopting the level 0 methodology following the UN/ECE Convention on Long-range Transboundary Air Pollution. Deposition data were available for the period 1992-1997, and acidity exceedances were referred to the main vegetation types present in the area. Results showed that most part of the Estate has a medium degree of vulnerability to acidification, and the corresponding risk of acidification deriving from the exceedances of atmospheric deposition was rather low. The study of soil chemical and microbiological properties included mainly total soil organic carbon (SOC), microbial biomass-C, biomass-C/SOC, soil respiration, and metabolic quotient (qCO2). Soil organic C metabolism has been discussed on the basis of the results from eight sampling sites.
Keywords: Acidification; Atmospheric depositions; Biological indicators; Critical loads; Soil microbial biomass; Soil organic carbon